Justicia thailandica, a new species of Acanthaceae from Thailand - Yi Tong; Yunfei Deng (PhytoKeys, 2019)
A new species of Justicia (Acanthaceae), J. thailandica, is described and illustrated from Thailand. The new species belongs to Justicia sect. Harnieria and is similar to J. quadrifaria and J. championii, but differs on account of the obviously densely white indumentum in the inflorescence bracts and calyx, ovate leaf blades with margin usually entire, spathulate inflorescence bracts and length ratio of calyx to mature capsule. It is assessed to be “Near threatened” (NE) according to IUCN Red List Category and Criteria. Pollen and seed morphology characters are also reported. Species of Justicia sect. Harnieria in Thailand are discussed and a key to the three recognized species is presented.